MUNICIPAL LIBRARIES: Digitization as a means of preserving and rescuing archival material and books. Ways to manage and avoid material damage. - NIKTA, MARINA (Qualitative and Quantitative Methods in Libraries, 2022)
Municipal Libraries have a significant number of rare and valuable publications as well as unique archival material. This valuable property was acquired essentially both by institutions of the Municipalities and intellectuals who provided archival and photographic material, by purchases of entire libraries of important Greek scholars and by donations of citizens who responded to the call, offering generous items from their personal collections. Until recently, the rarity of this material imposed on its management a series of prohibitions that made research difficult. The adoption of digital technology in the field of Closed Collections has come to change the data and facilitate research, simulating it to a large extent with that of open access collections. The purchase of a scanner specially designed for the digitization of rare editions, completely abolished the previous regime of banning the reproduction and study of rare material, since the only way we had until then, was photocopying. Now, any internal or external user can request to digitize whatever and as much material as needed. The reading needs of the users formed the basis for the creation of a Digital Library of rare material. The digitization and electronic cataloging of these books was deemed necessary, not only because it contributed to the substantial, albeit virtual, enrichment of the electronic catalog of the Municipal Libraries, but also because it digitally saved an extremely distressed printed material of maximum importance. The purpose of this article is to clarify issues of organization and structure of Municipal Libraries, in order to support actions for the preservation of their collections as well as the possibility of preserving the collections in combination or not with digitization actions. In addition, in a second level, the possibility of the institutions to support the digitization programs is explored and at the same time, the opinion of the experts of the profession regarding the sustainability of their digitized collections is presented. At the same time, the steps-instructions that should be followed before, during or after the digitization are briefly presented in order to avoid any damage to the archival material to be digitized.